Geospatial Dynamics of Urban Irrigation Agricultural Land Use for Sustainable Income Generation on the Jos Plateau (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Urban agriculture has become increasingly significant in African cities as a strategy for food security, income generation, and sustainable urban development. This study employed geospatial techniques, anchored in the Sustainable Livelihoods Framework (SLF), to map and analyze market gardening activities and land use changes in Jos South Metropolis, Nigeria, over a ten-year period (2014–2024). The research addresses critical knowledge gaps regarding the spatio-temporal dynamics and sustainability challenges of urban agriculture in Jos Metropolis, where comprehensive data on arable farming activities had been lacking despite extensive crop cultivation. High-resolution satellite imagery with 15 cm spatial resolution was acquired from the National Space Research and Development Agency (NASRDA) for both time periods and processed using ArcGIS 10.8 software. Through systematic on-screen digitization, spatial analysis, and change-detection algorithms, the study quantified changes in agricultural land use, settlements, and water bodies. Extensive fieldwork involved systematic reconnaissance of Jos South Local Government Area (LGA) to identify active market gardening sites, establish ground control points, and conduct interviews with local farmers and agricultural extension agents. Results revealed that market gardens covered 9.59 km² in 2014, declining to 9.03 km² in 2024, representing a 5.84% reduction. Conversely, settlements expanded dramatically from 43.82 km² to 79.32 km², a 34.76% increase, while water bodies decreased marginally from 4.57 km² to 4.46 km², highlighting increasing pressure on water resources driven by urbanization. The study identified key constraints to sustainable urban agriculture including land tenure insecurity, with 63% of dry-season farmers being landless; limited access to irrigation water; pest and disease pressure; inadequate fertilizer supply; and increasing competition for land from urban development. Field surveys documented diverse cropping systems, with farmers cultivating temperate vegetables such as tomatoes, lettuce, cabbage, carrots, and Irish potatoes throughout the year using fadama lands along river channels and mine ponds. The intensive cropping systems documented included plots undergoing three cropping cycles per year, demonstrating both the productivity potential and sustainability challenges. The findings align with global evidence that urban agriculture persists in the face of urbanization, serving multiple livelihood, ecological, and social functions. The research demonstrates the capability of remote sensing and GIS in monitoring urban agricultural dynamics and provides baseline data for urban planning and agricultural policy formulation. The study recommends establishing agricultural zones in fadama areas, strengthening extension services, enacting secure land tenure policies, and fostering rural–urban production synergies to sustain this vital economic sector in the face of rapid urbanization.